Monoclonal antibodies differentiating between monocytic and nonmonocytic variants of AML. - Linch, D; Allen, C; Beverley, P; Bynoe, A; Scott, C; Hogg, N (1984)
Blast cells from 70 cases of acute myeloid leukemia (AML), with a preponderance of monocytic variants (M4 and M5), were stained with a panel of 10 monoclonal antibodies (MoAb) that react with normal myeloid cells. Two McAb, UCHMI and UCHALF, stained cells from nearly every case of M4 and M5 leukemia, but not cells from cases of M1/M2 leukemia. Two other antibodies, E11 and UC45, were also specific for the monocytic leukemias, but stained cells from a lesser proportion of cases. The antibodies TG1, OKM1, Smø, DA2, 28, and 5.5 stained a differing proportion of cases in both the M1/M2 and M4/M5 subtypes. Routine morphology and alpha-naphthyl acetate esterase (ANAE) staining were largely in agreement with the antibody findings, though the interpretation of the fluoride sensitivity of ANAE was apparently misleading in 10% of cases. It is concluded that these antibodies, particularly UCHMI and UCHALF, will be of considerable value in the more precise subtyping of AML and that some of this panel of antibodies will be valuable tools for the investigation of normal monocytic differentiation.